The phenomenon of emotional leadership in the managerial activities of managers (Actual Problems of Psychology in Educational Institutions, 2021)
The article is devoted to the problem of emotional leadershipwithin the managerial activities of managers. It is given the formulafor effective interaction of such psychological phenomena as emotionalleadership, social mobility and self-realization of personality. It is analyzeda regression model, where the effectiveness of the leader’s interactionwith society depends on personal factors related to the level of selfawareness, self-control, ability to empathize and social skills. It is revealedthe components of emotional leadership and defined their features in thecontext of the managerial activities of managers. It is determined themain characteristics of leader with developed emotional intelligence. Theimportance of emotional intelligence in the managerial activities of modernleaders is analyzed
Keywords: leadership; emotional leadership; management; emotional intelligence; social mobility; self-awareness